Species diversity and status of key marine habitats in Cu Lao Cham Marine Protected Area, Quang Nam province - Nguyen Van, Long; Vo Si , Tuan; Nguyen Van, Vu (Vietnam Journal of Marine Science and Technology, 2021)
In recent years, several studies relating to assessments of marine biodiversity conducted in the Cu Lao Cham Marine Protected Area. However, the data and information from these studies have not been synthesized. This study was based on analyses of data and information from 22 sites of coral reefs, ten sites of rocky shores, five sites of seagrass beds, eight sites of Sargassum beds, and four sites on soft-bottom communities conducted in 1994, 2004, 2008, 2016 and 2017. A total of 976 species belonging to 223 families of 9 common groups (330 species corals, 277 species of fishes, 156 species mollusks, 91 species seaweeds, 71 species of polychaetes, 24 species crustaceans, 22 species of echinoderms and five species of seagrasses) were found. Coral reefs supported the highest number of species (779 species) compared to that of the soft- bottom (135 species), seagrass beds (124 species), and rocky shores (58 species). In general, most of the coral reefs and seagrass beds were not in good condition, with a low mean cover of hard corals (24,8 ± 15,7%) and of seagrasses (11,9 ± 11,6%). Densities of target macro-invertebrates and fishes with large sizes and high value were extremely low, giving exception of a high density of large fishes of fusiliers, snappers, emperors, rabbitfishes, queenfishes, barracuda) found at Bai Dau Tai, Bai Bac, Hon Mo, Hon Tai and the submerged reefs (Ran La, Ran Manh).